A responsabilidade dos pais na formação espiritual dos filhos : um entendimento bíblico-teológico - Montanha, Joel (2010)
This paper discusses the necessity of a conscious and active participation of parents in the spiritual development of children, considering that the family is recognized as the main former of spirituality of children. The research is developed from biblical and theological principles. Necessities, characteristics and forms of communication with children within their different age group are analyzed for an adequate spiritual nurture. Since this is a recurrent theme in the discussion about nurture at homes, the research seeks to comprehend the role of parents in the nurture of children and the possible contrast found in the care which is provided at today s Christian homes. The first part of the paper deals with the origins of the rational principles of human being, that is, the ways in which the knowledge is acquired. Afterwards, we approach the concepts about God, the nature of evil, the salvific plan, the means of grace, self esteem and freedom of choice, elements that cause actions, which may influence the infant to choose their own Judeo-Christian spirituality. Finally, the teaching and the socialization within the groups of children aged 0-10 are under the parents responsibility.